Philippine medical thesaurus on anatomy musculoskeletal system and sense organs in Kapampangan - Cayanan, Vicente Ron M.; Castillo, Africa R. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
One element of a better disease management is a good relationship between doctors and patients and it can be attained with proper diagnosis and proper care. But then some diseases are often misdiagnosed due to language differences between the doctor and patient. As a result communication barrier can be considered as one of the major restraints for better disease management. Hence, still no books are available to translate the standard medical terms into Filipino language or other Philippine dialects.
The Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila took effort to collaborate a Multilingual Philippine Medical Thesaurus to produce a tool for Filipino use and lessen the difficulty and confusion in medical terms.
This paper focused on Musculoskeletal System and Sense Organs facets of the seventeen (17) facets under anatomy in Medical Subject Headings (MeSH). Dictionaries that were ranked by experts were used by the researcher to translate the terms gathered in MeSH to Kapampangan. There were also series of interviews done by the researcher in both medical and non-medical professionals to determine the validity of the terms and also because the focused facets in this study are highly technical, the interviews played an important factor in the translation of terms. The making of this thesaurus was based on ISO 5964 which is a standard guideline in thesaurus construction.
Out of the two hundred sixty eight (268) terms that were downloaded, one hundred seventy five (175) came from the Musculoskeletal System while the remaining ninety three (93) came from Sense Organs. The researcher was able to translate one hundred twenty (120) terms, ninety four (94) came from Musculoskeletal System and the remaining twenty six (26) came from the facet of Sense Organs. From the remaining one hundred forty eight terms that have no Kapampangan translation ten (10) terms had scope notes.
The completion of this paper would be vital for the development and construction of the thesaurus and would greatly help not only to promote the language consistency of medical field but also to preserve even a part of Kapampangan language and culture.
Vita.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Kapampangan -- Medicine; Subject headings, Kapampangan -- Musculoskeletal system; Kapampangan language -- Medical Kapampangan